Reproduction Performance of Magelang Duck Evaluated by Histological Preparation - Yosephine Laura Raynardia Esti Nugrahini; Monica Sonia Indri Pradipta (Universitas Tidar, 2018)
Abstract This study aims to increase duck population in their origin distribution area Sempu, Ngadirojo Village, Secang, Magelang district. The increasing is evaluated by Magelang duck reproduction performance in this area. Ngadirojo was the origin area of duck Magelang distribution but unfortunately the population has begun to decline due to the presence of commercial farmers who sell this type of duck out of the region. Most of the people in Ngadirojo also maintain semi-intensive methods so that reproduction and maintenance performance is poorly controlled due to low performance including reproduction. The data evaluated includes mature age, mature sex weight, egg laying, egg production per week, egg fertility, egg hatchability, incubation time, mating method, and reproductive technology that had been applied. Data collection was grouped on intensive and semi-intensive farms in Sempu sub-village, Ngadirojo village, Secang sub-district, Magelang regency. Evaluation has been carried out through the manufacture of histological preparations for female reproductive ducks of production age (6-12 months) on intensive and semi-intensive farms. Reproductive performance data were analyzed descriptively and data on histology preparations were displayed as support. The results obtained by farms in the Sempu sub-village are semi-intensive duck breeders, ducks are carried out in to the rice fields at certain hours. No intensive breeders were found in the Sempu hamlet, therefore comparative data as intensive breeders were obtained in the Tempuran area, Magelang district. Based on the survey, Magelang duck farmers in Sempu hamlet had normal reproductive performance but when evaluated through histology preparations it was found that the reproductive organ tissue of Magelang ducks which were intensively maintained were more productive. Key words : Magelang duck, histological preparation, Secang sub-district, Reproduction.